Insights into Physicochemical Assessment of Shade Tree Litter Biomass in Tea Plantations of Terai Region - Ghosh, Arindam; Majumder, Soumya; Sarkar, Sahadeb; Bhattacharya, Malay (International Journal of Sustainable Agricultural Research, 2022)
Tea is a major plantation crop and the socioeconomic pillar of Terai region of West Bengal. Use of various inorganic fertilizers may have increased the crop production but affected the environment badly. Importance of biomass of different trees in accumulation of carbon had long been known but few studies on characterization of biomass accumulation are reported. So, selection of different species for getting the good amount of organic nutrients is important. In tea plantation, various leguminous trees are used as shade trees. This research, conducted in the tea plantation of University of North Bengal, has provided some approaches which could possibly reduce the application of inorganic fertilizers. Different tests on physicochemical parameters, micronutrients status, biomass etc. were conducted with the collected plant litters. The results of this comparative analysis suggested and validated the beneficial effects of each shade tree in organically maintaining nutrient profile of tea plantation soil.